Molecular Layer Deposition of Pyrrone Thin Films by Oxidative Polymerization - Saba Ghafourisaleh; Marko Vehkamäki; Anton Vihervaara; Chao Zhang; Mikko J. Heikkilä; Markku Leskelä; Matti Putkonen; Mikko Ritala (Advanced Materials Interfaces, 2023)
Abstract In this paper, the deposition of pyrrone thin film materials by molecular layer deposition (MLD) is reported for the first time using pyromellitic dianhydride (PMDA) and 3,3'‐diaminobenzidine (DAB) as monomers, and ozone as a promoting precursor. Besides ozone, the effect of water, hydrogen peroxide, and oxygen is also tested to promote the growth of MLD thin films. Ozone as a strong oxidant is the best reactant in this process. Two precursor pulsing sequences are tested and both result in pyrrone films. With the DAB+O3+PMDA sequence, growth per cycle (GPC) of 1.2 Å is obtained at 250–300 °C, whereas with the DAB+PMDA+O3 sequence, GPC of 1.5 Å is obtained. When only DAB and O3 are used, indamine films with GPC of 1.0 Å are obtained. The films are characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and atomic force microscopy. Chemical, thermal, and electrical properties of the films are also investigated. The films are stable in acidic and basic solutions and organic solvents, and they withstand 300 °C when annealed in air.